Effective Context and Familial Conditions on Drug Addiction Relapse: A Qualitative Study - Azam Pilevari; Seyed Mohammad Hossein Javadi (Kerman University of Medical Sciences, 2019)
Introduction: Family is one of the causative factors of initiation and relapse of addictive behaviors. Family is like a double-edged sword due to the fact that family may function both as a supporter of drug users as well as a shield to protect them against their withdrawal hardships, and also a cause of drug addiction relapse. Lack of sufficient knowledge and domestic studies on this issue, make it necessary to deal with this issue through investigation. So, this study aimed to identify effective context and familial conditions on addiction treatment non-retention. Method: This study is a part of a larger study on the role of the family in addiction treatment retention. It was conducted by Grounded theory in Tehran in 2016. Sampling was performed using purposive sampling from clients of medium-term residential centers and continued until data saturation. Data were collected using semi-structured interviews with 12 drug users and 12 members of their families. Data were analyzed using Strauss and Corbin coding methods. Results: The main theme of this study was family conflict. Family conflict includes subthemes such as enmeshment, triangulation, stressful behavior, communication avoidance and diminishing communication, non-operating threats, which were intensified by emotional imbalance (interference conditions). Based on the participants' experiences, causality conditions affecting drug addiction relapse include false belief and external locus of control in a context of users and family's unawareness. Conclusion: Users and family's insight and perception of the nature of addiction result in negative emotions, and accordingly, lead to dysfunctional interactions that provide context for drug addiction relapse.